A Halogen Bond Induced Triple Helicate Encapsulates Iodide - Massena, Casey J. (Angew Chem Int Ed Engl, 2016)
The self-assembly of higher-order anion helicates in solution remains an elusive goal. Here we present the first triple helicate to encapsulate iodide in organic and aqueous media as well as the solid state. The triple helicate self-assembles from three tricationic arylethynyl strands and resembles a tubular anion channel lined with nine halogen bond donors. Eight strong iodine⋯iodide halogen bonds and numerous buried π-surfaces endow the triplex with remarkable stability even at elevated temperatures. We suggest that the natural rise of a single-strand helix renders its linear halogen bond donors non-convergent. Thus, the stringent linearity of halogen bonding is a powerful tool for the synthesis of multi-strand anion helicates.